PERINDOPRIL: THE POSSIBILITY OF ANTIHYPERTENSIVE AND RENOPROTECTIVE THERAPY - O. V. Dralova; M. L. Maksimov (Столичная издательская компания, 2016)
Blood pressure (BP) control in patients with chronic kidney disease is one of the most pressing problems in modern cardiology and nephrology. Perindopril therapy reduces cardiovascular risk in patients with arterial hypertension and nephropathy, provides adequate BP control and target organs protection.